Impact of green space on residents' wellbeing: A case study of the Grand Canal (Hangzhou section) - Xia, Yuke (Frontiers in Public Health, 2023)
This research aims to discuss the importance of the combination of cultural heritage management and green development for urban development by analyzing the upgrading and renovation case of the Grand Canal (Hangzhou section). In recent years, green development has risen to prominence as a paradigm shift from traditional urban development. In addition, culture has received more attention as an engine to drive urban development. This research uses a hybrid approach to examine the importance of combining green development with cultural heritage management. The qualitative method is an interview analysis of 13 residents living in the Hangzhou section of the Grand Canal. Based on the analysis of multiple water quality variables in Hangzhou from 1998 and 2014 to 2021, the empirical results prove that it is feasible to integrate green development (environment and economy) into the cultural heritage management of the case study area. This thesis further proves that only through understanding the relationship between cultural heritage and green development can a virtuous cycle of development be created, thereby promoting the continuous development of a unique and historically significant urban area in a virtuous cycle. This study suggests that in the development of mega-cities, although the preservation and inheritance of historical and cultural heritage conflict with the green development of modern cities, a successful sample has been explored in Hangzhou where the two factors can be mutually compatible and promote each other, which, in the end, allows local residents to have a greater sense of gain.